The Relationship between Smoking and Susceptibility to HIV Infection: A Two-Sample Mendelian Randomization Analysis - Min-Rui Yu; Wei Hu; Song Yan; Meng-Meng Qu; Yan-Mei Jiao; Fu-Sheng Wang (Biomedicines, 2024)
Smoking is prevalent among people living with the human immunodeficiency virus (HIV), and it increases morbidity and mortality in this population. However, due to ethical constraints, there is limited information on the effects of smoking on susceptibility to HIV infection. To investigate whether smoking is associated with an increased susceptibility to HIV infection, we conducted a two-sample Mendelian randomization (MR) study using summary statistics from genome-wide association studies of individuals of European ancestry who have ever smoked (n = 99,996) and have HIV (n = 412,130). The random-effects inverse-variance weighted estimation method was used as the study’s primary approach, with the MR-Egger regression and the weighted-median method as complementary approaches. Using 100 single-nucleotide polymorphisms of genome-wide significance as instrumental variables for smoking, we observed a significant association between smoking and HIV infection (odds ratio 5.790, 95% confidence interval [1.785, 18.787], and p = 0.003). Comparable results were obtained using the weighted-median method. Our findings implied that smoking is probably associated with increased susceptibility to HIV infection. Given the exploratory nature of this study, further research is needed to confirm this relationship.